Beyond the Numbers : Understanding the Institutions for Monitoring Poverty Reduction Strategies. - Bedi, Tara, 1978- (World Bank e-Library., 2006)
"Beyond the Numbers: Understanding the Institutions for Monitoring Poverty Reduction Strategies provides lessons on the design and functioning of monitoring systems which are based on the experiences of twelve countries that have implemented poverty reduction strategies. The book's focus is on the institutional arrangements of poverty reduction monitoring systems - the rules and processes that bring the various actors and monitoring activities together in a coherent framework - rather than on any particular activity or actor. This book provides practitioners with lessons and guidance, diagnostic tools, and a summary of the progress made in the twelve countries that have embraced the poverty reduction strategy."--Jacket